The effect of rehabilitation exercises, especially in improving the range of motion and the degree of pain for those with partial rupture of the ankle joint ligaments - Ahmed, EmadKadhom; Adnan Hatrosh, Nibras (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research came in preparing special exercises for the case of lacerations in the ankle joint of a sample of athletes to reduce the period of interruption from training and to speed up the return to practicing the specialized activity as soon as possible by using some physical exercises to reduce the effects of injury, which ensures the recovery of the player's efficiency and physical fitness. Special exercises for the case of lacerations in the ankle joint in a sample of athletes to reduce the duration of interruption of training and speed up the return to the practice of specialized activity as soon as possible by using some physical exercises to reduce the effects of injury, which ensures the recovery of the player's efficiency and physical fitness, and the researcher used The experimental approach in the style of designing the individual station is equivalent, and the research sample included a number of patients with soft tissue injuries (muscles, ligaments) with partial tears, and their number was 8 injured from different activities and games. Ankle, a test to determine the degree of pain for the ankle joint), and the rehabilitation exercises began in the first unit on Wednesday, 19/6/2019, at three in the afternoon, and the exercises ended on Thursday, 29/7/2019, and the treatment period was (6 weeks), and the number of rehabilitation units using magnets was 18 units. the researcher concluded that the accompanying rehabilitative exercises prepared by the researcher have a positive effect in improving the range of motion of the ankle joint and relieving the degree of pain, and the researcher recommends emphasizing the necessity of adopting the program Prepared by the accompanying researcher in physiotherapy centers, conducting more research and studies of various injuries that affect athletes individually and in their acute stages in order to deepen the specificity of each injury and prepare its own rehabilitation programs.